The National War Labor Board and Postwar Industrial Relations - Fisher, Paul (Quarterly Journal of Economics, 1945)
The "common law of industrial relations, " 483. — Collective bargaining: ordered, 487; geographic scope, 489; job specification and classification, 491; office and clerical salaries, 492; incentive wage systems, 492; vacations, 494; equality of treatment, 495; racial and other discrimination, 493; severance pay, 497; seniority, 493; union representatives, 499; union security, 500; extension of contracts, 503; administration and enforcement of agreements, 505; grievance settlement, 505; union responsibility, 510; preventive administrative practices, 514; labor courts, 515. — Disputes arising outside of collective bargaining agreements: inter-union disputes, 516; compulsory arbitration, 516; mediation, 519. — Conclusion, 522.